Remote work during the COVID-19 pandemic - Kacprowska, Krystyna (Civitas et Lex, 2021)
The beginning of the COVID-19 virus epidemic is having an impact on radical changes in the labor market. The difficult economic situation is a challenge for employers, candidates, and recruiters. In recent months, the recruitment market has seen a decline in the work forces, redundancy, and a reduction in salaries. As a result of this situation, some workplaces have introduced the remote work model. The possibility of remote work can be a good solution for many employees, but in some cases, it can be a significant inconvenience, especially for employees who have underage children and perform their work duties at home. The aim of the article is to present the positive and negative aspects of remote work during the COVID-19 pandemic. The research presented in the article was aimed at assessing changes in working conditions and starting remote work. The positive effects of changes in workplaces include saving time, adjusting work to personal needs, and work-life balance. The disadvantages of taking up remote work include lack of direct contact with co-workers, blurring of boundaries between private and professional life, the necessity of maintaining a constant presence at work, lack of social ties and isolation, which have been identified as the most significant obstacles to remote work during the COVID-19 pandemic. Despite the negative aspects of working remotely, the respondents more often declared their willingness to work remotely also after the pandemic ends.